Pragmatic variations in giving advice in L2 by Malaysian postgraduate students: the situational effects - Farashaiyan, Atieh; Muthusamy, Paramasivam (Canadian Center of Science and Education, 2016)
The present study attempted to describe the giving advice strategies utilized by Malaysian postgraduate students in confronting different situations. In addition, it examined the effects of the situational factors of social distance, power, and imposition on the students’ choice of giving advice strategies. Another objective was to categorize the challenges students face in the production of giving advice in English. One hundred and ten Malaysian postgraduate students majoring in different fields voluntarily participated in this study. A Written Discourse Completion Task Questionnaire and semi-structured interviews were utilized for data collection procedure. The results of the questionnaire illustrated that the respondents tended to use more direct strategies to give advice. The first most frequently strategy used by the respondents was obligation strategy, 53.38%., mood derivable strategy with 30.08% as the second most frequently used strategy and performative as the third one, while no respondent used the hedged performative and want statement strategies in any of the situations. The respondents also opted out the same strategies almost with similar frequency in most of the situations. It means that the choice of strategies was not different in terms of the three situational variables of power, distance and imposition. In addition, the results of interviews showed that the challenges they face in the production of advice giving include expression, structure, culture, social values, first language, gender, age and educational background of the interlocutors. This study has some implications for second language acquisition research and intercultural communication.